2014
DOI: 10.1021/la502245s
|View full text |Cite
|
Sign up to set email alerts
|

Transition and Stability of Copolymer Adsorption Morphologies on the Surface of Carbon Nanotubes and Implications on Their Dispersion

Abstract: In this study, the adsorption morphologies as well as stability and transitions of a commercial dispersant copolymer (BYK 9076) on the surface of multiwalled carbon nanotubes (MWCNTs) were studied using Fourier transform infrared and UV−vis spectroscopy, dynamic light scattering, and electron microscopy techniques. The results show that the dispersion of carbon nanotubes in ethanol does not increase continuously with increasing copolymer/CNT ratio, which is correlated with the adsorption morphologies of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Although a higher degree of dispersion can be achieved by increasing energy, ultrasonication can damage the structure of the particle, inducing defects such as dislocation, formation of amorphous carbon on the CNTs, shortening them, thereby decreasing their aspect ratio, and interrupting the cohesion between the tubes and the host matrix [41][42][43].This is why, recently, a novel method of using acoustic generator of the pulsating jet has been proposed to disperse CNTs in the aqueous environment without damage or disintegration [44]. Therefore, an optimal ultrasonication energy that balances desirable dispersion with minimal induced damage has been proposed [27], which in turn depends on the CNT concentration, diameter, length, and the solvent media [45,46]. For instance, Islam et al [47] recommended a low power bath sonication to preserve the length and structure of CNTs, Sabolkina et al [42] concluded, based on UV-vis spectra, that sonication should last more than 30 minutes to achieve satisfactory dispersion.…”
Section: Mechanical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a higher degree of dispersion can be achieved by increasing energy, ultrasonication can damage the structure of the particle, inducing defects such as dislocation, formation of amorphous carbon on the CNTs, shortening them, thereby decreasing their aspect ratio, and interrupting the cohesion between the tubes and the host matrix [41][42][43].This is why, recently, a novel method of using acoustic generator of the pulsating jet has been proposed to disperse CNTs in the aqueous environment without damage or disintegration [44]. Therefore, an optimal ultrasonication energy that balances desirable dispersion with minimal induced damage has been proposed [27], which in turn depends on the CNT concentration, diameter, length, and the solvent media [45,46]. For instance, Islam et al [47] recommended a low power bath sonication to preserve the length and structure of CNTs, Sabolkina et al [42] concluded, based on UV-vis spectra, that sonication should last more than 30 minutes to achieve satisfactory dispersion.…”
Section: Mechanical Methodsmentioning
confidence: 99%
“…Further increasing the surfactant dosage above the critical amount results in the formation of multilayer surfactant molecules, which cannot bring about improvement in particle dispersion [42] and may even cause reduction in the repulsion forces [39], while also encouraging CNT-flocculation [57] and negatively affecting hydration [39,47,58]. It is worth mentioning, based on observations of Korayem et al [46], there is another possible morphology for the adsorption of copolymers on the surface of the CNTs, called hemi-micelle. The dispersion of CNTs with hemi-micelle coating is more stable than that of random coating but not as efficient as cylindrical coating.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…The challenge of dispersion becomes even more pronounced when nanotubes are blended into highly viscous epoxy resins. Different approaches have been reported to achieve the uniform dispersion of CNTs in various media, namely: (a) mechanical methods such as ultrasonication [33,34], high shear mixing [35] and calendaring [29,36,37]; (b) covalent functionalization [30,[38][39][40], and (c) physical surface treatment of CNTs by using dispersants such as surfactants [41], bio macromolecules [42,43] and copolymers [44][45][46][47][48]. Each method has its benefits and limitations.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, their poor solubility and strong preference toward making bundles in commonly used organic and aqueous solvents hinder easy and environmentally-friendly processing as well as advances in biological applications. Therefore, a variety of functionalization methods, such as ultra-sonication, chemical surface modification, and non-covalent functionalization by using surfactants and block copolymers, [4][5][6][7][8][9] have been developed to modify the CNT surfaces and improve their dispersibility in a wide range of solvents. Non-covalent functionalization methods based on physical surface treatments, in particular, are considered to be a promising and robust strategy, because any surface-modification induced suppression in intrinsic CNT properties can be minimized.…”
Section: Introductionmentioning
confidence: 99%